2020
DOI: 10.1038/s41598-019-57315-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro testing of a funnel-shaped tip catheter model to decrease clot migration during mechanical thrombectomy

Abstract: one limitation of mechanical thrombectomy (Mt) is clot migration during procedure. this might be caused by abruption of the trapped thrombus at the distal access catheter (DAc) tip during stentretriever retraction due to the cylindrical shaped tip of the DAc. Aiming to solve this problem, this study evaluates the proof-of-concept of a new designed funnel-shaped tip, in an experimental in vitro setting. two catheter models, one with a funnel-shaped tip and one with a cylindrical-shaped tip, were compared in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Since the thrombus is disproportionally larger than the diameter of common cylindrical catheters, there is a risk that it will be abraded against the catheter wall. We have now been able to confirm the superiority of the funnel-shaped extension from previously published preliminary tests with the new prototype catheter [11] .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Since the thrombus is disproportionally larger than the diameter of common cylindrical catheters, there is a risk that it will be abraded against the catheter wall. We have now been able to confirm the superiority of the funnel-shaped extension from previously published preliminary tests with the new prototype catheter [11] .…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, the Department of Neuroradiology at the University Hospital Mainz, Germany, developed a novel catheter designed to prevent thrombus loss and fragmentation at the catheter wall during stent retriever retraction. A recent proof-ofprinciple-study showed a better recanalization rate for the funnel-shaped tip compared to a standard cylindrical tip [11] . Our prototype catheter (PC) was developed on this basis.…”
Section: Introductionmentioning
confidence: 98%
“…A total of 160 MTs were carried out. Results from the preliminary study Tanyildizi et al 2 were included in the Chandler loop group. Please refer to the owchart (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We compared the funnel-shaped tip featuring a larger inner-opening diameter (d = 2.5mm) to a standard tip (d = 1.5mm) model, in terms of functionality and e cacy for mechanical thrombectomy in an in vitro setup. In our rst in vitro study, we observed higher recanalization rates of up to 90% using the modi ed funnel-shaped tip compared to 50 to 60% for the standard tip 2 . Consequently, the proof-of-concept for a newly designed funnel-shaped tip was deemed viable for continuing further in vitro experiments, this time including a greater case number (N = 160) and…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation